2017
DOI: 10.1096/fj.201700400rr
|View full text |Cite
|
Sign up to set email alerts
|

EGCG ameliorates high‐fat– and high‐fructose‐induced cognitive defects by regulating the IRS/AKT and ERK/CREB/BDNF signaling pathways in the CNS

Abstract: Obesity, which is caused by an energy imbalance between calorie intake and consumption, has become a major international health burden. Obesity increases the risk of insulin resistance and age-related cognitive decline, accompanied by peripheral inflammation. (-)-Epigallocatechin-3-gallate (EGCG), the major polyphenol in green tea, possesses antioxidant, anti-inflammatory, and cardioprotective activities; however, few reports have focused on its potential effect on cognitive disorders. In this study, our goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 66 publications
3
70
1
Order By: Relevance
“…39) It was found that EGC-M5 and EGC-M7 had an inhibitive effect on ACE enzyme in vitro and hypotensive effects in vivo. 39) Kiryu et al 40) reported that ACE inhibitors sig- Data are expressed as the mean ± SEM (n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39) It was found that EGC-M5 and EGC-M7 had an inhibitive effect on ACE enzyme in vitro and hypotensive effects in vivo. 39) Kiryu et al 40) reported that ACE inhibitors sig- Data are expressed as the mean ± SEM (n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicate that metabolites play a crucial role in metabolic regulation in the body following green tea intake. Yashi et al 41) reported that EGCG administration reversed insulin resistance and neuroinflammation in the brain of C57BL/6J mice fed a long-term high-fat and high-fructose diet (HFFD). Recently, Unno et al 33) discovered that EGC-M5 could significantly prolong neurite length of human neuroblastoma SH-SY5Y cells, and increase the number of these cells significantly.…”
Section: Resultsmentioning
confidence: 99%
“…As with other polyphenolic compounds, EGCG has been studied for its antioxidant, anti-inflammatory, and anti-obesity effects [ 135 , 136 , 137 ]. When treated with EGCG for 16 weeks, mice placed on a HFD and 10% fructose solution resisted obesity development and displayed better CNS insulin sensitivity than HFD-fed obese control mice [ 138 ]. Further, EGCG attenuated neuroinflammation by lowering TNF-α mRNA and phosphorylation of inflammatory markers p38 and NF-kβ in the brain.…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 99%
“…UPLC‐TOF MS/MS analysis demonstrated that the main active compounds of CLE were catechin, quercetin, kaempferol, and their derivatives, which have been evidenced as neuroprotective phytochemicals (Costa, Garrick, Roquè, & Pellacani, 2016; Hussein, Mohamed, & Omar, 2018; Sutcliffe, Winter, Punessen, & Linseman, 2017). Moreover catechin, an essential constituents of tea polyphenol, has been evidenced in upregulation of CREB/BDNF signaling (Ding, Ma, Man, & Lv, 2017; Mi et al., 2017). Therefore, the neuroprotective effect of CNC leaves might be a combined effect of these active compounds.…”
Section: Resultsmentioning
confidence: 99%